2019
DOI: 10.1002/bmc.4619
|View full text |Cite
|
Sign up to set email alerts
|

UPLC–QTOF/MS‐based metabolomics reveals the mechanism of chronic unpredictable mild stress‐induced hypertension in rats

Abstract: Hypertension is a common chronic disease, and it is the strongest risk factor for cardiovascular disease. Recently, the number of patients with hypertension-related complications has increased significantly, adding a heavy burden to the public health system. It is known that chronic stress plays an important role in the pathogenesis of cardiovascular diseases such as hypertension and stroke. However, the impact of hypertension on the dysfunctions induced by chronic stress remains poorly understood. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…Unlike a previous study in rats with chronic mild stress 25 , we found lower LPCs in the intervention group following the lifestyle intervention, with different correlations with physiological parameters based on the acyl chains. The stress relief, as indicated by a lower stress index, was positively associated with the suppressed LPCs in the intervention group: LPC(14:0), (16:1), and (20:4) (Cluster B, Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike a previous study in rats with chronic mild stress 25 , we found lower LPCs in the intervention group following the lifestyle intervention, with different correlations with physiological parameters based on the acyl chains. The stress relief, as indicated by a lower stress index, was positively associated with the suppressed LPCs in the intervention group: LPC(14:0), (16:1), and (20:4) (Cluster B, Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to the positive association between LPC(20:4) with stress index, the free fatty acid (20:4) form, has been previously suggested as a marker of depression and stress in human 18 and rats 25 , respectively. LPC(22:5) in the intervention group was also associated with inflammation and adiposity.…”
Section: Discussionmentioning
confidence: 94%
“…Lyso-phosphatidylcholine (20:4) has been suggested as a marker of stress and depression in rats and humans ( Adams et al, 1996 ; Wu et al, 2019 ). Although phosphatidylcholines are involved in normal cognition ( Haus et al, 2009 ), and chronic stress can cause depression due to decreases in phosphatidylcholines ( Ren et al, 2018 ), high levels as seen in the present experiment are due to enhanced fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of the CUMS-induced high BP model was done in accordance with previous descriptions. 15 In short, rats were exposed to chronic unpredictable mild stress for 4 weeks; in particular, tails were clamped for 1 min on Monday, food was deprived for 24 h on Tuesday, cages were shaken for 5 min on Wednesday, rats were forced to swim in water at 4 1C for 5 min on Thursday, day and night were reversed for 24 h on Friday, cages were kept cold-wet for 24 h on Saturday, and rats were bound up for 6 h on Sunday. After the last treatment, rats were anesthetized with 10% chloral hydrate (100 g/0.4 mL, intraperitoneal (i.p.…”
Section: Animals and Treatmentsmentioning
confidence: 99%